Analysis of Students’ Problem Solving Ability Based on Metacognition Ability in Set Topic - Pardiansyah, Riko; Kamid, Kamid; Hariyadi, Bambang (Indonesian Journal of Science and Mathematics Education, 2021)
This mixed method research was conducted to find out how students' problem-solving abilities were seen from the metacognition ability on the topic set. The population in this study were class XII students of MAN 2 Jambi City in the 2020/2021 academic year. The sample in this study was selected using the simple random sampling technique. The results of this study indicate that students' problem solving abilities based on students' metacognitive abilities on the topic of the set are in the good category. Metacognition ability can make it easier for students to solve mathematical problems that have been given. Metacognition indicators that seem to have been mastered by students in this study are awareness, regulation, and evaluation.